INDONESIAâS MONETARY POLICIES AND ITS EFFECTS IN STOCK MARKET IN COVID-19 ERA - Irfan Rasyadi Saputra, Muhammad
The COVID-19 virus that is now spreading throughout the world has made it difficult in various sectors for many countries. Research proves that COVID-19 makes various countries experience a decrease in economic activity, and even some reach the crisis. Therefore, various countries are trying to implement monetary policy to improve the country's economy. The main objective of this study is to investigate the relationship between Rupiah stabilization through Monetary Policies and its impact on the stock market stabilization during the COVID-19 situation. Multiple regression in logarithm form was conducted to achieve this research. This method was used to identify the relationship between Rupiah exchange rate against USD as the dependent variable and FX swap, Domestic non deliverable forward (DNDF), Jakarta Composite Index (JCI), Jakarta Interbank Spot Dollar Rate (JISDOR), COVID-19 case as the independent variable. The multiple regression model was validated using the ordinary least square (OLS) assumption, which must be achieved to create a valid model. The analysis has been done in this study. This research investigate the relationship between Rupiah exchange rate stability against two monetary instruments, namely FX swap and DNDF during the pandemic and including reference rate, namely JISDOR. There was a positive correlation between Rupiah and DNDF, while the relationship between Rupiah stability and FX swap results in a negative correlation. Moreover, JISDOR as a reference rate has a positive correlation between Rupiah and JISDOR. This research analyzed the relationship between Rupiah's stability and the stock market, and the results showed a negative relationship between Rupiah's stability and the stock market. Based on the results in this study, Rupiah exchange rate stability influenced FX swap, DNDF, JISDOR, and the stock market. Therefore, to maintain Rupiah exchange rate stability during the COVID-19 pandemic, monetary policies are essential. Bank of Indonesia, as a central bank, can optimize its policy instruments through DNDF and FX swap for exchange rate stabilization.